Schizandrin C regulates lipid metabolism and inflammation in liver fibrosis by NF-κB and p38/ERK MAPK signaling pathways - Chen, Panpan; Wang, Rong; Liu, Fangbin; Li, Shengnan; Gu, Yanqiu; Wang, Lei; Yuan, Yongfang (Frontiers in Pharmacology, 2023)
Liver fibrosis is considered a sustained wound healing response and metabolic syndrome, and its therapy is of great significance for chronic liver disease. Schizandrin C, as one lignan from hepatic protectant Schisandra chinensis, can depress oxidative effect and lipid peroxidation and protect against liver injury. In this study, C57BL/6J mice were used to estimate liver fibrosis model by CCl4, and Schizandrin C exerted anti-hepatic fibrosis effect as evidenced by decreased ALT, AST and TBIL activities in serum, lower hydroxyproline (HYP) content, recuperative structure and less collagen accumulation in liver. In addition, Schizandrin C reduced the expressions of alpha-smooth muscle actin (α-SMA) and type Ι collagen (collagen Ι) in liver. In vitro experiments also revealed that Schizandrin C attenuated hepatic stellate cells (HSCs) activation in both LX-2 and HSC-T6 cells. Furthermore, lipidomics and quantitative real-time PCR analysis revealed Schizandrin C regulated lipid profile and related metabolic enzymes in liver. Besides, the mRNA levels of inflammation factors were downregulated by Schizandrin C treatment, accompanied with lower protein levels of IκB-Kinase-β (IKKβ), nuclear factor kappa-B (NF-κB) p65 and phospho (p)-NK-κB p65. Finally, Schizandrin C inhibited the phosphorylation of p38 MAP kinase (p38 MAPK) and extracellular signal-regulated protein kinase (ERK), which were activated in CCl4 fibrotic liver. Taken together, Schizandrin C can regulate lipid metabolism and inflammation to ameliorate liver fibrosis by NF-κB and p38/ERK MAPK signaling pathway. These findings supported Schizandrin C as a potential drug for liver fibrosis.